The Politics of Blended Health Sector Financing in Uganda: Unpacking the World Bank’s Global Financing Facility - Kiiza, Julius; Nassimbwa, Jacqueline; Mulumba, Moses (Tanzania Journal of Development Studies, 2019)
This paper examines the politics of blended financing with reference to the World Bank-inspired Global Financing Facility for maternal, newborn, child, and adolescent health (RMNCAH) in Uganda. Critical literature review was conducted, followed by interviews with government technocrats, multilateral agencies (World Bank, WHO and UNICEF), civil society organizations and selected district health officers. Our main finding is twofold. Procedurally, blended finance takes the trodden path of developmental paternalism characterized by asymmetrical power relations between donors (who determine fundable priorities) and beneficiaries (whose inclusion hardly counts). Substantively, however, Uganda’s Investment Case uses concessional IDA credit worth US$110m, multidonor trust funds worth $30m and a SIDA grant of US$25m. This raises the total to $165m, with a grant component of 33.33%, far above the 25% recommended by the OECD. The emerging conclusion is simple: blended finance is imperfect, but is not ‘dead aid’ a la Dambisa Moyo (2010).
Keywords: Politics; Health Sector Financing; World Bank’s Global Financing Facility